TYPES OF INSECTS ASSOCIATED WITH POTATO PLANTS (SOLANUM TUBEROSUM L.) AND THE INCIDENCE OF THE DISEASE IN MODOINDING, NORTH SULAWESI, INDONESIA - Eva L. BAIDENG; Hanry J. LENGKONG; Terry M. FRANS; Roni KONERI; Hanny PONTORORING (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The concept of smart forest is rather recent, being adapted from the climate smart agriculture concept, which has appeared in 2010. The forest situated in this category should fulfill the following criteria: increased income and productivity, improved resilience and reduces greenhouse gases. In addition, climate-smart forestry in mountain regions tries to situate forests from the mountain area based on their adaptation towards climatic changes, carbon stocks, biodiversity or other synthetic indices. The present article tries for the first time the framing of alder forests from the Southern Carpathian Mountains based on 16 indices regarding their site and stand characteristics. Alder stands from this area are generally located on plain fields, at low altitudes and on average or superior bonity stations. However, only 3.6% of them can be situated in the smart forest category. These stands are indicated on humid and rich soils, while their exploitation should be realized when they reach an age of 60-70 years